Modernizing Insurance Regulation 2014
DOI: 10.1002/9781118766798.ch7
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Risk and Regulation of the U.S. Insurance Industry

Abstract: This paper analyzes the characteristics of U.S. insurers for purposes of determining whether they are systemically risky. More specifically, primary factors (size, interconnectedness, and lack of substitutability) and contributing factors (leverage, liquidity risk and maturity mismatch, complexity and government regulation) associated with systemic risk are assessed for the insurance sector. A distinction is made between the core activities of insurers (e.g., underwriting, reserving, claims settlement, etc.) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…7. Cummins and Weiss (2014) show that life insurers more involved in writing group annuity business are more likely to score higher on the market-based measure of systemic risk, SRISK, developed by Acharya et al (2010).…”
Section: Solvency Concerns Emergementioning
confidence: 98%
“…7. Cummins and Weiss (2014) show that life insurers more involved in writing group annuity business are more likely to score higher on the market-based measure of systemic risk, SRISK, developed by Acharya et al (2010).…”
Section: Solvency Concerns Emergementioning
confidence: 98%
“…Prior studies have made important and unique contributions to the literature on market structure-performance in the insurance sector. However, researchers have pointed out that market concentration in certain insurance lines may be disguised by the overall market measures (Cummins and Weiss, 1992) and the findings of the overall industry may not apply to a certain insurance line (Carroll, 1993). Thus, research based on line-specific measures is necessary.…”
Section: China's Engineering Insurance Industrymentioning
confidence: 99%
“…As engineering insurance is heavily influenced by the nature of construction activity, it is characterized by high risk, complex risk factors, multi-stage, multi-insured and comprehensive insurance coverage (Liu et al, 2007(Liu et al, , 2018Anchen et al, 2018). The findings of the overall insurance (or life/non-life insurance) market may not apply to engineering insurance (Cummins and Weiss, 1992;Carroll, 1993). Therefore, it is crucial to conduct a macroscopic study on the engineering line to investigate this specific insurance industry, which is the motivation of this study.…”
mentioning
confidence: 99%
“…The purpose of government in applying the risk-based capital method is not only to protect the interests of the public as insurance policyholders, but also to adjust to the development of national insurance industry. Cummins and Weiss (2014) stated that the US system that uses RBC as a solvency indicator disregards operational risk, catastrophe risk and qualitative criteria, such as risk management systems and corporate governance. Therefore, their research indicated that RBC is not an accurate predictor of insurance solvency.…”
Section: Introductionmentioning
confidence: 99%